DEVELOPING STUDENT'S LISTENING ABILITY THROUGH INTERACTIVE LISTENING - Gultom, Mannara (2009)
Teaching of listening for second language or foreign language learners can not be neglected. It should have priority in the classroom. It is assuming greater and greater importance in foreign language classroom, (Nunan, 2002). It implies that with listening there will be language development within the learners. However, the students find difficulties in comprehending when listening integrated with other skills (speaking and writing), (Suryanti, 2002). Based on the researcher's teaching simulation experience in Maal-Ihsan Balaendah in Bandung, the researcher got a big surprise to see the students feel very enthusiastic and interested in attending the listening class integrated with speaking and writing activities. Therefore, to prove it the researcher did a true experiment to the eleventh class of science program in a Senior High School in Serui in Kepulauan Yapen (one of provinces in Papua). The title of the research is "Developing the Student's Listening Ability through Interactive listening". The research questions of this study were 1) Is Interactive Listening effective to develop student's listening ability?, 2) What makes interactive listening able to develop student's listening ability, and 3) what more provoke student's involvement. The data collecting applied in this research were test, questionnaire, interview and linguistic evidence. The test data was analyzed by t-test, the questionnaire data was analyzed by Likert Scale, and interview data was analyzed by transcribing, categorizing, and interpreting the data. The findings revealed that teaching listening integrated with speaking activities (Interactive Listening) was significant in developing the students' listening ability. It goes with Brown (2001) the student's listening ability would be enhanced when speaking activities were integrated. The main point of Interactive Listening that can develop student's listening ability is the speaking task developed from spoken language. It could encourage the students to be more active to listen to the spoken language, to express what they have heard. Speaking activities in a dialog form more provokes the student's involvement and the lack of vocabulary is the main factor causing difficulty to comprehend the spoken language.